Testing the Reliability and Construct Validity of a Chinese Translation of BASC-3-SRP for 12- to 18-Year-Old Youth. (9th September 2019) - Tan, Tony Xing; Yi, Zhiyao; Kamphaus, Randy W.; Wang, Yan; Li, Zhengjie; Cheng, Ke
We tested the reliability and construct validity of a Chinese translation of one of the forms of the Behavior Assessment System for Children (3rd Edition)–Self-Report of Personality for adolescent 11- to 21-year olds (BASC-3-SRP-A). The BASC-3-SRP-A yields 16 subscales that form four composite scales. Data were obtained from 444 12- to 14-year olds (Group 1; girls: 59.0%) and 759 15- to 18-year olds (Group 2; girls: 69.2%). For both groups, Cronbach's alphas for most of the 16 subscales were higher than .70 and were higher than .83 for the four composite scales. Confirmatory factor analysis (CFA) using Mplus 8 on the combined sample yielded support for the construct validity of the Chinese translation of the BASC-3-SRP-A. Findings support the use of BASC-3-SRP-A among Chinese youth.